A holistic approach to marine eco-systems biology - Karsenti, Eric; Bork, Peer; Arendt, Detlev (PLoS biology, 2011)
The structure, robustness, and dynamics of ocean plankton ecosystems remain poorly understood due to sampling, analysis, and computational limitations. The Tara Oceans consortium organizes expeditions to help fill this gap at the global level.
Gesehen am 18.05.2017